Long-Term Monarchical Survival in the Middle East: A Configurational Comparison, 1945-2012 - André Bank; Thomas Richter; Anna Sunik (German Institute of Global and Area Studies (GIGA), 2013)
The survival of eight monarchies during the Arab Uprisings of 2011 has put center stage the fundamental question about the durability of this subtype of authoritarian regime. Seen from a broader historical perspective, however, the idea that monarchies have an inherent advantage in retaining power is less evident: a number of authoritarian monarchies broke down and subsequently became republics (Egypt 1952, Iraq 1958, North Yemen 1962, Libya 1969, Iran 1979), while others survived (Bahrain, Jordan, Kuwait, Morocco, Oman, Qatar, Saudi Arabia, UAE). To account for these divergent long-term pathways we compare the 13 current and former Middle Eastern monarchies, as well as their different trajectories. Using a fuzzy set qualitative comparative analysis (fsQCA), we concentrate on five central explanatory factors derived from previous research on Middle Eastern monarchies - namely, US military support, rent revenues, family participation, the monarch's claim to legitimate rule and anti-government protest. Our findings support the existence of two broad pathways to monarchical survival - linchpin monarchies, like Jordan and Morocco, versus the dynastic Gulf monarchies - and also reveal a possible third pathway, one which shares linchpin characteristics, but relates to cases on the Arabian Peninsula (Oman, the historical Imamate in North Yemen, and Saudi Arabia).
Keywords: 300; Middle East monarchies; regime survival; family participation; rents; legitimacy claims; US military support; anti-government protests; Arab Uprisings